The Strength of Educator, Scientist, and Enlightener Is Humanity - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 2000)
This article represents not only scientific pedagogical heritage of the professor J. Laužikas, but talks about the professor’s humanity - his sensitiveness, love of children, trying to perceive the child. The professor in his scientific works analyses the problems of humanistic education, pedagogical communication, knowledge of child, educational psychology. Many ideas of professor are important till now – ideas about the essence of education, the individualization, differentiation and humanization of education and other.